Impact of Dual Placement and Routing on WDDL Netlist Security in FPGA. (24th December 2013) - Amouri, Emna; Mehrez, Habib; Marrakchi, Zied
Abstract : The wave dynamic differential logic (WDDL) has been identified as a promising countermeasure to increase the robustness of cryptographic devices against differential power attacks (DPA). However, to guarantee the effectiveness of WDDL technique, the routing in both the direct and complementary paths must be balanced. This paper tackles the problem of unbalance of dual-railsignals in WDDL design. We describe placement techniques suitable for tree-based and mesh-based FPGAs and quantify the gain they confer. Then, we introduce a timing-balance-driven routing algorithm which is architecture independent. Our placement and routing techniques proved to be very promising. In fact, they achieve a gain of 95%, 93%, and 85% in delay balance in tree-based, simple mesh, and cluster-based mesh architectures, respectively. To reduce further the switch and delay unbalance in Mesh architecture, we propose a differential pair routing algorithm that is specific to cluster-based mesh architecture. It achieves perfectly balanced routed signals in terms of wire length and switch number.